2006
DOI: 10.3317/jraas.2006.013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Clamping of Renin Gene Expression Induces Hypertension and Elevation of Intrarenal Ang II Levels of Graded Severity in Cyp1a1-Ren2 Transgenic Rats

Abstract: Introduction. Transgenic rats with inducible angiotensin II (Ang II)-dependent hypertension (strain name: TGR[Cyp1a1-Ren2]) were generated by inserting the mouse Ren2 renin gene, fused to the cytochrome P450 1a1 (Cyp1a1) promoter, into the genome of the rat. The present study was performed to characterise the changes in plasma and kidney tissue Ang II levels and in renal haemodynamic function in Cyp1a1-Ren2 rats following induction of either slowly developing or malignant hypertension in these transgenic rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
153
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(187 citation statements)
references
References 37 publications
32
153
2
Order By: Relevance
“…Plasma angiotensin II concentration was determined by radioimmunoassay as described previously. 26,27 Plasma aldosterone concentration was measured by radioimmunoassay with the use of a DPC aldosterone kit (Mitsubishi Chemical Medience, Tokyo, Japan). The plasma concentration of nitric oxide metabolites (NO x ) was determined by the Griess method with the use of a Nitrate/Nitrite Colorimetric Assay Kit (Cayman Chemical, Ann Arbor, MI, USA), as previously described.…”
Section: Plasma Analysismentioning
confidence: 99%
“…Plasma angiotensin II concentration was determined by radioimmunoassay as described previously. 26,27 Plasma aldosterone concentration was measured by radioimmunoassay with the use of a DPC aldosterone kit (Mitsubishi Chemical Medience, Tokyo, Japan). The plasma concentration of nitric oxide metabolites (NO x ) was determined by the Griess method with the use of a Nitrate/Nitrite Colorimetric Assay Kit (Cayman Chemical, Ann Arbor, MI, USA), as previously described.…”
Section: Plasma Analysismentioning
confidence: 99%
“…Plasma renin activity was determined by radioimmunoassay with the use of renin RIA beads (Abbott Japan, Tokyo, Japan). Plasma angiotensin II (Ang II) concentration was determined by radioimmunoassay as described previously, 14,15 and serum aldosterone concentration was measured by radioimmunoassay with the use of a DPC aldosterone kit (Mitsubishi Chemical Medience, Tokyo, Japan). Extended details appear in the Supplementary Material online.…”
Section: Measurement Of Metabolic and Hormonal Parametersmentioning
confidence: 99%
“…We have demonstrated that at a dose of 0.3% (wt/wt), chronic dietary administration of I3C induces malignant hypertension in Cyp1a1-Ren2 transgenic rats (27,28,31,32). Malignant hypertension is a severe form of hypertension characterized by rapidly increasing blood pressure, pressure diuresis and natriuresis, severe renal vasoconstriction and ischemia, activation of the renin-angiotensin system, microangiopathy, hemolytic anemia, and development of retinopathy (23,47,48).…”
mentioning
confidence: 99%
“…In essence, induction of the Cyp1a1 promoter by I3C is used to drive hepatic expression of the Ren2 renin gene. In this transgenic rat model, induction of the Cyp1a1 promoter by dietary administration of I3C results in a fixed level of expression the Ren2 renin gene and in the development of ANG II-dependent hypertension (23,27). This transgenic rat model, therefore, allows genetic clamping of extrarenal renin gene expression and induction of ANG IIdependent malignant hypertension consequent to fixed levels of elevated plasma renin that are not subject to normal homeostatic regulation (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation